Grain-boundary diffusion of titanium in Zr-1 wt.%Nb alloy under irradiation with a pulsed electron beam; Russian Physics Journal; Vol. 66, No. 11 - Grabovskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Teresov A. D. Anton Dmitrievich; Kruglyakov M. A. Mark Aleksandrovich; Lomygin A. D. Anton Dmitrievich (2024, 2024)
Title screen